2017
DOI: 10.1159/000481827
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Fatigue in Patients with Sarcoidosis

Abstract: Background:Little is known about physical activity in daily life among patients with sarcoidosis. Fatigue is a frequent and disabling symptom that might negatively affect physical activity levels. Methods: In patients with sarcoidosis, we measured physical activity (steps per day) by accelerometry (SenseWear Armband) for 1 week. We assessed lung function (DLCO, FVC), exercise capacity (6-min walking distance . Results: We investigated 57 patients with sarcoidosis (mean age 50 years, 56% male, mean DLCO 73% pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
4
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 37 publications
3
25
4
6
Order By: Relevance
“…The results of this study show that DL PA is decreased in adult patients with stage IV sarcoidosis and that SPD is significantly associated with VO 2 max. Our results are in agreement with three previous studies evaluating physical activity in patients with sarcoidosis . Kostorz et al evaluated the comorbidities associated with DL PA in 30 patients with sarcoidosis, albeit without precise radiological staging and found that the patients had walked a mean (±SD) SPD of 5214 (±2699).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The results of this study show that DL PA is decreased in adult patients with stage IV sarcoidosis and that SPD is significantly associated with VO 2 max. Our results are in agreement with three previous studies evaluating physical activity in patients with sarcoidosis . Kostorz et al evaluated the comorbidities associated with DL PA in 30 patients with sarcoidosis, albeit without precise radiological staging and found that the patients had walked a mean (±SD) SPD of 5214 (±2699).…”
Section: Discussionsupporting
confidence: 92%
“…However, it is important to note that Bahmer et al included only three patients with chronic sarcoidosis stage IV in their study cohort, which could explain the differences between their and our results. Indeed, the mean (±SD) SPD recorded in that study (7490 ± 3007) was higher than in our study (6395 ± 4119).…”
Section: Discussioncontrasting
confidence: 82%
See 3 more Smart Citations